Association of stress hyperglycemia ratio and poor long-term prognosis in patients with myocardial infarction with non-obstructive coronary arteries - Fuad A. Abdu; Jassur Galip; Penglong Qi; Wen Zhang; Abdul-Quddus Mohammed; Lu Liu; Guoqing Yin; Ayman A. Mohammed; Redhwan M. Mareai; Rong Jiang; Yawei Xu; Wenliang Che (Cardiovascular Diabetology, 2023)
Abstract Background Stress hyperglycemia ratio (SHR) is a novel biomarker of true acute hyperglycemia condition and is associated with a worse prognosis in patients with myocardial infarction (MI). However, the effects of SHR in the setting of MI with non-obstructive coronary arteries (MINOCA) have not been investigated. This study aimed to explore the association between SHR and long-term clinical outcomes among MINOCA patients. Methods A total of 410 MINOCA patients were included in the final analysis of this study. The patients were divided into three groups based on the SHR tertiles: [SHR1 group (SHR ≤ 0.73), (n = 143); SHR2 group (SHR 0.73–0.84), n = 131; and SHR3 group (SHR ≥ 0.84), n = 136]. Follow-up for major adverse cardiovascular events (MACE) was conducted on all patients. Cox regression and Kaplan–Meier curve analysis were used to evaluate the relationship between SHR and MACE. The receiver operating curve (ROC) analysis was applied to obtain the optimal cut-off value of SHR for predicting clinical MACE. Results A total of 92 patients developed MACE during the mean 34 months of follow-up. A significant increase in MACE was observed in the SHR3 group compared to the SHR1 and SHR2 groups (35.3% vs. 15.4% and 16.8%, respectively; P < 0.001). The Kaplan–Meier curves demonstrate that SHR3 patients had the highest MACE risk compared to SHR1 and SHR2 patients (log-rank P < 0.001). In addition, when both SHR tertiles and diabetes status were considered, those with SHR3 and diabetes had the highest hazard of MACE (log-rank P < 0.001). Multivariate Cox regression analysis showed that the SHR3 is associated with a 2.465-fold increase in the risk of MACE (adjusted HR, 2.465; 95% CI 1.461–4.159, P = 0.001). The ROC curve analysis showed that the optimal SHR cut-off value for predicting clinical MACE among MINOCA was 0.86. Conclusion Our data indicates, for the first time, that SHR is independently associated with poor long-term prognosis in patients suffering from MINOCA. The optimal SHR cut-off value for predicting clinical MACE among MINOCA patients was 0.86. These findings suggest that SHR may play a potential role in the cardiovascular risk stratification of the MINOCA population.